Effectiveness of Coaching by School Improvement Partners through Good Relationship and Professionalism Skills Practiced - Zalina Mohd Tahir; Nabihah Mohd Salleh (Research in Social Sciences and Technology- OpenED Network, 2018)
School administrators consisting of Principals and Headmasters (PGB) play a significant role in leading the school to achieve excellence. To ensure that excellence is achieved within the timeframe stipulated, the PGB received guidance from fellow coaches known as School Improvement Partners (SIP). The coaching process requires mutual understanding between the two parties so that it can work smoothly and effectively (Narimawati, 2007) without any conflict of ideologies. This study is to identify the effectiveness of the coaching of SIP through the good relations and professional skills practiced during the ongoing coaching. A total of 212 PGB as respondents and data were analyzed using SPSS version 23 for the descriptive analysis, while AMOS version 22 is used for advanced statistics Structural Equation Modeling. The study found that the goodness of fit model by SIP coaching is good with reading of chi-square/df=2.203, CFI= .969, p=0.00 and RMSEA=.076. Good relationship with professional coaching sessions have contributed a total of 71% (R2=.71) to the effectiveness of the coaching as well as it helps to increase the PGB confidence in the development of schools. This finding confirms that coaching by SIP directly acts as a catalyst for the success of the school and to complete the needs of mission and vision of the Ministry of Education, Malaysia.